2019
DOI: 10.35333/erd.2019.7
|View full text |Cite
|
Sign up to set email alerts
|

Effects of Different Er:YAG Laser Parameters on Debonding Forces of Lithium Disilicate Veneers: A Pilot Study

Abstract: The aim of this study was to investigate the effects of different Er:YAG laser application parameters on shear bond strength values of all-ceramic restorations cemented to different tooth surfaces. Materials and Methods: Thirty lithium disilicate ceramic disc specimens (thickness of 1 mm and diameter of 3 mm) were fabricated and cemented by using a dual-cure resin cement to 30 non-carious, extracted mandibular incisors, which were divided into 2 as; tooth reduction on enamel and on dentin. Six test groups (n=5… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

2
1
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(3 citation statements)
references
References 21 publications
2
1
0
Order By: Relevance
“…All selected parameters succeeded in debonding PLVs with different periods, which is in agreement with the studies of Goznel et al (2019), AlBalkhi et al (2017), Iseri et al (2014) Oztoprak et al (2012), and Morford et al (2011), in investigating the efficiency of Er:YAG laser in debonding PLVs using different debonding techniques.…”
Section: Discussionsupporting
confidence: 89%
See 1 more Smart Citation
“…All selected parameters succeeded in debonding PLVs with different periods, which is in agreement with the studies of Goznel et al (2019), AlBalkhi et al (2017), Iseri et al (2014) Oztoprak et al (2012), and Morford et al (2011), in investigating the efficiency of Er:YAG laser in debonding PLVs using different debonding techniques.…”
Section: Discussionsupporting
confidence: 89%
“…Very little data have been published in this field with different veneer removal techniques. Morford et al (2011) investigated the efficiency of the Er:YAG laser in debonding PLVs using one technique with many different laser parameters; Iseri et al (2014) concluded that the application of the Er:YAG laser decreased the bond strength of laminate veneers; Oztoprak et al (2012) used different application times of the Er:YAG laser and concluded that they were effective in debonding ceramic laminate veneers by softening the adhesive resin; Goznel et al (2019) investigated the effects of different Er:YAG laser application parameters on shear bond strength values of all‐ceramic restorations cemented to different tooth surfaces, and they concluded that as the depth of prepared tooth structure increases, minimal values of laser parameters such as frequency and energy are needed for debonding of the same restoration type. With regard to temperature considerations, Alikhasi et al (2019) used the Er,Cr:YSGG laser to debond different types of ceramic PLVs and concluded that there is no significant difference for debonding time among them without increasing pulpal temperature over 1°C.…”
Section: Introductionmentioning
confidence: 99%
“…When the samples were examined under SEM, over 70% of the teeth structures were covered, although certain spots lacked resin cement. This demonstrated that the resin cement's exterior surface was softened by a comparable laser finding, as seen in Figure 4, which was similar to the results of the study by Karagoz et al [28].When the resin cement layer failed cohesively, resin cement remained on the inner surface of the laminate veneers as shown in Figures 5-7 and the tooth structure as shown in Figure 8, according to the SEM analysis of the teeth and laminate veneers. However, the teeth surfaces had more cement fragments visible.…”
Section: Discussionsupporting
confidence: 86%